2009
DOI: 10.1080/00480169.2009.36905
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofMycobacterium bovisfrom brushtail possums with non-visible lesions

Abstract: The finding of M. bovis infection in possums with non-visible lesions identified a potential deficiency of declaring possum populations free of M. bovis on the basis of absence of macroscopic lesions. The culturing of pools of selected tissues from multiple animals without visible lesions can be used to reduce laboratory costs of possum surveys without a major reduction in the ability to detect M. bovis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In possums, it has been established that many individual animals in early stages of infection will show no gross lesions, but when pooled cultures of critical tissues, including lung and lymph nodes, are processed, many additional M. bovis-infected animals are found. 12 This is not surprising to experienced researchers working with tuberculosis, since BTB lesions start at the microscopic level and progress to form larger macroscopic lesions. One study found that 10.9% of possums surveyed had visible lesions, but when pooled cultures for M. bovis were conducted, the prevalence of infection increased by an additional 8.5%.…”
Section: Brushtail Possums In New Zealandmentioning
confidence: 99%
See 1 more Smart Citation
“…In possums, it has been established that many individual animals in early stages of infection will show no gross lesions, but when pooled cultures of critical tissues, including lung and lymph nodes, are processed, many additional M. bovis-infected animals are found. 12 This is not surprising to experienced researchers working with tuberculosis, since BTB lesions start at the microscopic level and progress to form larger macroscopic lesions. One study found that 10.9% of possums surveyed had visible lesions, but when pooled cultures for M. bovis were conducted, the prevalence of infection increased by an additional 8.5%.…”
Section: Brushtail Possums In New Zealandmentioning
confidence: 99%
“…One study found that 10.9% of possums surveyed had visible lesions, but when pooled cultures for M. bovis were conducted, the prevalence of infection increased by an additional 8.5%. 12 Although culturing nonlesioned tissues adds both time and expense to the diagnostic process, it is important not to declare geographic areas or wildlife populations tuberculosis free without microbiological confirmation.…”
Section: Brushtail Possums In New Zealandmentioning
confidence: 99%
“…Culture of pooled samples of frequently infected tissue types from possums without lesions is occasionally used in research projects and, increasingly, in surveys conducted to determine whether TB is absent from possums (de Lisle et al 2009 ). In places where possum numbers are low, it is more cost-effective to increase detection sensitivity through culture rather than relying on visual detection of gross tuberculous lesions in additional possums.…”
Section: Ecology and Epidemiology Of Tb In Possumsmentioning
confidence: 99%
“…In surveys of four wild populations in which all commonly infected tissue sites were cultured, 44% of those culture-positive for M. bovis had no visible lesions (de Lisle et al . 2009 ). Another study suggests that only 11% had no visible lesions (Cooke 2000 ), while in a third study about one-third had no lesions (Lugton 1997 ).…”
Section: Ecology and Epidemiology Of Tb In Possumsmentioning
confidence: 99%
“…As already noted, the EH area sensu lato was the subject of possum control operations in 1994/1995 and again in 2000/2001, and the adjacent areas to the north, east and south were deemed to have been brought under control progressively; however, an area immediately to the west was not brought under full control until the intensive operation of 2005. In that western area, M. bovis infection was common in deer, pigs, and possums until at least 2000 [6], and in May 2005 was confirmed by mycobacterial culture as still present at 11% prevalence in possums (n=93) in a moderate-high density population collected from a small (y200 ha) part of the adjacent western area ( [29] Table 1. Prevalence of culture-confirmed M. bovis infection cases (%) and sample sizes (in parentheses) of pigs from six main areas, by year of survey.…”
Section: Spatial Pattern Of Infectionmentioning
confidence: 99%